2010
DOI: 10.1007/82_2010_96
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IL-10 in Regulating Immunity to Persistent Viral Infections

Abstract: The immune system has evolved multipronged responses that are critical to effectively defend the body from invading pathogens and to clear infection. However, the same weapons employed to eradicate infection can have caustic effects on normal bystander cells. Therefore, tight regulation is vital and the host must balance engendering correct and sufficient immune responses to pathogens while limiting errant and excessive immunopathology. To accomplish this task a complex network of positive and negative immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
135
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(153 citation statements)
references
References 148 publications
5
135
0
6
Order By: Relevance
“…It has been shown that IL-10 can induce DCs apoptosis in vitro and substantially reduces the ability to effectively present antigens by suppression of DCs differentiation and maturation (Pinzon-Charry et al 2005). Suppression of antigen presentation in DCs is a keystone of immunotolerance; however this property is often utilized by viruses to limit the immune response during infection (Wilson and Brooks 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that IL-10 can induce DCs apoptosis in vitro and substantially reduces the ability to effectively present antigens by suppression of DCs differentiation and maturation (Pinzon-Charry et al 2005). Suppression of antigen presentation in DCs is a keystone of immunotolerance; however this property is often utilized by viruses to limit the immune response during infection (Wilson and Brooks 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, impairment of DCs maturation with dominance of immature phenotype, responsible for immunological tolerance, over mature phenotype engaged in antigen presentation and control of immunological reaction, was observed. It has also been shown that intensified IL-10 expression suppresses production of proinflammatory cytokines IL-12 and IFN-γ, which are crucial for induction of the Th1 response (Wilson and Brooks 2011).…”
Section: Discussionmentioning
confidence: 99%
“…34 A higher level of IL-10 mRNA expression was detected in monocytes from chronic HCV patients. 35 Studies have shown that HCV core protein induces KCs to secrete IL-10, in order to suppress secretion of pro-inflammatory factors. 36 IL-10 can also down-regulate major histocompatibility complex (MHC) class II molecules and costimulatory molecules, so interaction between KCs and NK cells, as well as their antigen-presenting function, can be suppressed.…”
Section: Il-10 and Tgf-βmentioning
confidence: 99%
“…36 IL-10 can also down-regulate major histocompatibility complex (MHC) class II molecules and costimulatory molecules, so interaction between KCs and NK cells, as well as their antigen-presenting function, can be suppressed. 35 IL-10 can not only terminate the immune response of T cells, but can also suppress T cells' immune activities toward the virus. 37 The direct influence of IL-10 on antigen-presenting cells can reduce the expression of the stimulating factor, inhibiting the secretion of cytokines and eventually making it hard to activate T cells.…”
Section: Il-10 and Tgf-βmentioning
confidence: 99%
See 1 more Smart Citation